ROAD TRAFFIC SAFETY AUDIT AT LOCAL OBJECT OF MINSK ROADWAY NETWORK - D. V. Kapsky; D. V. Mozalevsky; V. N. Kuzmenko; A. V. Korzhova; A. S. Polkhovskaya; E. N. Kostiukovich; N. V. Ariushevskaya (Наука и техника)
population of the Republic. Quality of the road traffic or its specific characteristics can be quantitatively estimated  in terms of losses and by that we understand social and economic value of non-obligatory expenses in road traffic. That is why any decision on road traffic organization must be estimated and optimized in accordance with its loss minimization criterion (accidental, economic and ecological).Research and Development Centre for Road Traffic at the BNTU Branch - “Research Division” has developed loss methodology in road traffic for  conflict objects – roads crossings and speed cushions. Such approach has made it possible to compare two alternative options for organization of road traffic at conflict objects. The paper considers an example of selection and substantiation of the accepted decision for an uncontrolled  T-junction with closely located pedestrian crossing in the Ya. Kolas Street, Building 12, Minsk. Planning and organizational and technical measures that increase road traffic safety and decrease economic and ecological losses have been developed on the basis of the executed investigations. The investigations and analysis of the existing conditions of the road traffic at the uncontrolled Ya.Kolas Street –Ya.Kolas off-street junction have revealed that the rate of total losses in the road traffic constitutes   nearly 92,000 c.u./year, including accidental losses – 7,900 c.u./year. Realization of the developed measures will permit to reduce the rate of accidental losses at pedestrian crossing approximately by 4,400 c.u./year with reduction of accidents by 50–55 %